2006
DOI: 10.21608/jesaun.2006.111354
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of Egyptian Talc Quality for Industrial Uses by Flotation Process and Leaching

Abstract: Talc is an industrial mineral that is widely used. It is always associated with other minerals, which determine the quality of talc samples for industrial purposes. Various operating variables control the natural floatability of talc. For enhancement of talc flotation, sodium hexametphosphate is used as a depressant for associated gangue minerals. In addition, oleic acid (in an equal mixture with kerosene) is used as an anionic collector. The results presented in this paper provided useful and important inform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…In a typical dry chlorination experiment, 5 g of talc sample was mixed thoroughly with 5 g of NH 4 Cl, and the mixture was transferred into a 100-mL crucible. The crucible was then placed in a muffle furnace and heated to 250 °C for 120 min.…”
Section: Dry Chlorinationmentioning
confidence: 99%
See 3 more Smart Citations
“…In a typical dry chlorination experiment, 5 g of talc sample was mixed thoroughly with 5 g of NH 4 Cl, and the mixture was transferred into a 100-mL crucible. The crucible was then placed in a muffle furnace and heated to 250 °C for 120 min.…”
Section: Dry Chlorinationmentioning
confidence: 99%
“…The mainstream gangue minerals in talc are magnesite (MgCO 3 ), carbonates, dolomite (CaMg(CO 3 ) 2 ), calcite (CaCO 3 ), serpentine, and chlorite (Mg 5 (Al,Fe)(Al, Si) 4 O 10 (OH) 8 ). The gangue minerals being hydrophilic in nature adversely affect the talc ore quality and hinder its industrial utilization [4,5]. For instance, the occurrence of iron oxide both on the surface and entrenched inside talc refutes its ingrained properties and limits its exploitation as an industrial precursor material.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, this technique applied on talc containing a considerable amount of associated minerals, is not possible for the same reasons explained above. Also, it is not directly applicable to industrial processes because of its high cost (Feng and Aldrich, 2004;Jaramillo et al, 2005;Perez-Maqueda et al, 2005;Ahmed et al, 2007). Jaramillo et al (2005) have reported that acid leaching was more effective than froth flotation to remove iron oxides from talc, mainly by dissolution.…”
Section: Introductionmentioning
confidence: 99%